2017
DOI: 10.1111/jcmm.13264
|View full text |Cite
|
Sign up to set email alerts
|

A positive feedback loop promotes HIF‐1α stability through miR‐210‐mediated suppression of RUNX3 in paraquat‐induced EMT

Abstract: Irreversible pulmonary fibrosis induced by paraquat (PQ) poisoning is the major cause of death in patients with PQ poisoning. The epithelial–mesenchymal transition (EMT) is postulated to be one of the main mechanisms of pulmonary fibrosis. Here, we investigated the role of miR‐210 in PQ‐induced EMT and its relationship with hypoxia‐inducible factor‐1α (HIF‐1α). Western blotting, immunofluorescence, immunoprecipitation and other methods were used in this study. We found that miR‐210 expression was significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 38 publications
2
11
1
Order By: Relevance
“…MiRNAs have also been shown to regulate of RUNX3 expression. miR-130b has been shown to decrease expression of RUNX3 in gastric tumour cells,24 and miR-210 was described to suppress RUNX3 expression in epithelial cells 25. However, we did not observe any significant correlation between mir-130b and mir-210 expression and RUNX3 expression levels in pDCs of these patients (see online supplementary table S2, supplementary figure S2).…”
Section: Resultscontrasting
confidence: 53%
“…MiRNAs have also been shown to regulate of RUNX3 expression. miR-130b has been shown to decrease expression of RUNX3 in gastric tumour cells,24 and miR-210 was described to suppress RUNX3 expression in epithelial cells 25. However, we did not observe any significant correlation between mir-130b and mir-210 expression and RUNX3 expression levels in pDCs of these patients (see online supplementary table S2, supplementary figure S2).…”
Section: Resultscontrasting
confidence: 53%
“…Recently, extensive evidence has demonstrated that epithelial‐mesenchymal transition (EMT) functions importantly in the invasion and metastasis of various epithelial tumours . The differentiation process that epithelial cells can down‐regulate epithelial properties and acquire mesenchymal features is commonly known as EMT.…”
Section: Introductionmentioning
confidence: 99%
“…Down-regulated miR-17-5p promoted PQ-induced degeneration of dopaminergic neurons in Neuro-2a cells (Wang et al, 2018a). Increased miR-210 expression after PQ poisoning aggravates the progression of pulmonary fibrosis through enhancing the stability of hypoxia-inducible factor-1 α, which promotes PQinduced epithelial-mesenchymal transition (Zhu et al, 2017). These studies indicate that miRNAs participate in different types of PQ-induced cell damage.…”
Section: Discussionmentioning
confidence: 84%